South Africa - Fraser, Sean, author 624233 (Cape Town : Struik ; London : New Holland [distributor], 2005)
When a burning sun dips low enough on the horizon to touch the brown-black earth, that is when South Africa is at its very best – a blazing expanse of broad landscapes of sea and veld, dusty savanna and equally dusty pavements. It is a vast country, extending from pristine coastal plain to rugged mountain passes across wide stretches of semi-desert and forest, hills and valleys. Even travelling South Africans are unprepared for the sheer scale and enormous diversity of this grand landscape.